Complexes of 2-amino-4-thiazoleacetic acid hydrazide(ATAH), salicylaldehyhde-2-amino-4-thiazoleacetic acid hydrazone (ATASH) And acetone-2-amino-4-thiazoleacetic acid hydrazone(ATAAH) each with nickel(II)sulphate As proposed drugs - Chinyelu Imo, Enedoh, Margaret; Francis C Imo , Ibe; Ngozi Imo, Ebosie, Patricia (African Journal of Education,Science and Technology (AJEST), 2016)
Complexes obtained from 2-amino-4-thiazoleacetic acid hydrazide [keto- (ATAH) and enol- (ATA) forms), salicylaldehyde- 2-amino-4-thiazoleacetic acid hydrazone (ATASH) and acetone -2-amino-4-thiazoleacetic acid hydrazone (ATAAH) were each complexed with nickel(II) sulphates. These complexes synthesized are hopefully meant to be further processed as potential drugs. The complexes were characterized by elemental analyses, conductance, infrared and electronic spectral studies. The ligands and complexes were screened for antimicrobial activity and one of the compounds was relatively active against the organism tested. The active compound is nickel-2-amino-4-thiazoleacetic acid hydrazide [Ni(ATAH)3]SO4 H2O. The electronic data indicate octahedral coordination for the all the complexes synthesized. The IR spectra data are diagnostic of bidentate coordination via the carbonyl oxygen and the azomethine, the SO42- anions are in their inner coordination spheres. The conductivity analyses indicate a non-electrolytic nature for the chelates.